Workshop on the Preparation of Red Ginger Herbal Beverages to Support Adolescent Girls' Reproductive Health - Ika Nur Saputri; Gita Amelia; Irma Nurianti (JURNAL PENGMAS KESTRA (JPK), 2026)
Adolescent reproductive health is a crucial aspect of improving the quality of future generations. One of the most common problems experienced by adolescent girls is dysmenorrhea, which can negatively affect learning activities, concentration, and overall quality of life. The utilization of red ginger (Zingiber officinale var. rubrum) may serve as an alternative approach to help manage this condition. This community service program aimed to enhance adolescent girls’ reproductive health literacy and improve their skills in processing red ginger into a herbal beverage that supports reproductive health. A participatory and educational workshop-based approach was implemented involving 30 eleventh-grade female students of SMA Swasta Nusantara Lubuk Pakam. The activities consisted of educational sessions, interactive discussions, demonstrations, and hands-on practice in preparing red ginger herbal drinks. Data were collected using knowledge questionnaires, skill observation sheets, and participant satisfaction questionnaires. The results demonstrated that the average knowledge score increased from 56.25% before the intervention to 88.75% after the program, representing an improvement of 32.5%. The greatest increase was observed in participants’ understanding of the benefits of red ginger as a herbal therapy, with an increase of 37%. Observation results revealed that participants achieved a good level of practical skill in processing red ginger, with an average success rate of 88.5%, while the highest achievement was recorded in the product presentation aspect (92%). Furthermore, participant satisfaction reached 94%, with the perceived benefits of the program receiving the highest score (97%). The red ginger processing workshop was proven effective in improving knowledge, practical skills, and awareness of adolescent girls regarding reproductive health, as well as promoting the utilization of red ginger as a non-pharmacological alternative to help manage dysmenorrhea.